Effect of green tea on gentamicin induced nephrotoxicity in Long Evans male rats - Nishat, Rahatul Jannat; Halim, Mohammad Rabiul; Islam, Md Motiul; Hamid, Tarikul; Ahmed, Kazi Nuruddin; Hasan, Rajib; Haque, Md Mazharul; Atiquzzaman, Md; Rahman, Asfaq Rafed; Das, Tarak Nath; Chowdhury, Rifat; Chowdhury, Israt Jahan; et al. (Bangladesh Critical Care Journal, 2022)
Background: The kidneys are a pair of essential excretory organs. It can be damaged by poisonous effects of chemicals, toxins, prolonged and uncontrolled use of drugs. Green tea is a popular choice of beverage being increasingly used in recent times which may have nephroprotective effect. Objectives: To observe the nephroprotective effect of green tea against gentamicin induced nephrotoxicity in Long Evans male rats. Methods: This study was carried out in the Department of Physiology, Sir Salimullah Medical College (SSMC), Dhaka from 1st July 2019 to 30th June 2020. A total number of thirty (30) apparently healthy Long Evans male rats, 90-120 days old, weighing between 150-200 g were taken for the study. After acclimatization for 14 days, they were divided into two groups, control group (Group A) and experimental group (Group B- green tea pretreated and gentamicin treated group). Control group was subdivided into group A1 (baseline control group) and group A2 (gentamicin treated control group). Each of this group was consisted of ten rats. All the rats received basal diet and baseline control group also received normal saline (1 ml/kg/day) for 28 days. Experimental group received ethanolic extract of green tea orally (300 mg/kg/day) for 28 days. Gentamicin treated control group and experimental group also received injection gentamicin intraperitoneally (80 mg/kg/day) for last 3 days (26th to 28th days) of the study period. All the rats were sacrificed on 29th day. After sacrifice blood (from heart) and kidney samples were collected. Serum levels of creatinine, urea and blood urea nitrogen (BUN), renal contents of malondialdehyde (MDA)and histopathology of kidney were done by using standard laboratory method to compare nephrotoxicity among experimental and control group. Statistical analysis was done by using Statistical Package of Social Science (SPSS) for windows version 22. Data were presented as mean±SD. One way ANOVA test, post hoc-Bonferroni test, paired‘t’ test and Fisher’s Exact test were done to compare the data as applicable. p value ≤ 0.05 was considered as level of significance. Results: The mean serum creatinine, urea, blood urea nitrogen (BUN) levels and mean malondialdehyde (MDA) concentration in kidney were significantly lower in green tea pretreated and gentamicin treated group than those of gentamicin treated control group but the levels were significantly higher in comparison to those of baseline control group. Moreover, abnormal histological findings of kidney was observed in 30% of rats in green tea pretreated and gentamicin treated experimental group but the abnormality was 100% and 0% in gentamicin treated and baseline control group of rats respectively. Conclusion: The present study reveals that green tea has nephroprotective effect against gentamicin induced kidney damage in Long Evans male rats. Bangladesh Crit Care J September 2022; 10(2): 127-134